Theoretical Studies of Nonlinear Generation Efficiency in a Bubble Layer - BARANOWSKA, Anna (Archives of Acoustics, 2013)
The aim of the paper is a theoretical analysis of propagation of high-intensity acoustic waves throughouta bubble layer. A simple model in the form of a layer with uniformly distributed mono-size sphericalbubbles is considered. The mathematical model of the pressure wave’s propagation in a bubbly liquidlayer is constructed using the linear non-dissipative wave equation and assuming that oscillations ofa single bubble satisfy the Rayleigh-Plesset equation. The models of the phase sound speed, changes ofresonant frequency of bubbles and damping coefficients in a bubbly liquid are compared and discussed. Therelations between transmitted and reflected waves and their second harmonic amplitudes are analyzed.A numerical analysis is carried out for different environmental parameters such as layer thicknesses andvalues of the volume fraction as well as for different parameters of generated signals. Examples of resultsof the numerical modeling are presented.